2017
DOI: 10.1080/00207543.2017.1366083
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supply chain relationships and integration on innovative capabilities and manufacturing performance: the perspective of rapidly developing countries

Abstract: The purpose of this research is to investigate the relationships between supply chain relationships/integration, innovative capabilities and manufacturing performance. The study adopts Institutional Theory and Resource Based View Theory to assess relationships in 171 organisations drawn from three rapidly developing countries-Brazil, India, China. Data was collected using the International Manufacturing Strategy Survey (IMSS VI) and analysed using Structural Equation Modelling. The study found that supply chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…In fact, it is acknowledged that there is a relationship between a firm and the institutional environment in which it operates, as this latter shape the guiding principles of the company and the way it complies with external rules, norms, and values (Oliver, 1991). This applies to a context, like the China, where culture and other national characteristics play a relevant role in shaping business practices and affecting related performance (Adebanjo, Teh and Ahmed, 2017). Although research has indicated that weak institutional environments have an impact upon agricultural supply chains and their performance (Yeboah et al, 2014), the choice of Chinese manufacturers context may also provide an understanding of weak institutional environment and its association to supply chain risk to achieve better performance in China.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is acknowledged that there is a relationship between a firm and the institutional environment in which it operates, as this latter shape the guiding principles of the company and the way it complies with external rules, norms, and values (Oliver, 1991). This applies to a context, like the China, where culture and other national characteristics play a relevant role in shaping business practices and affecting related performance (Adebanjo, Teh and Ahmed, 2017). Although research has indicated that weak institutional environments have an impact upon agricultural supply chains and their performance (Yeboah et al, 2014), the choice of Chinese manufacturers context may also provide an understanding of weak institutional environment and its association to supply chain risk to achieve better performance in China.…”
Section: Introductionmentioning
confidence: 99%
“…Such analytical tools allow organizations to integrate analytical models into their business processes, supporting the design of business strategies and enhancing decision-making capabilities [26]. By applying advanced AI technologies such as ML and cognitive services against the data coming in from the manufacturing process, organizations get value-added insights into data.…”
Section: Artificial Intelligence Conceptualization and Technologiesmentioning
confidence: 99%
“…For instance, since one of IJPR's aims is to publish research concerned with 'manufacturing strategy, policy formulation and evaluation' (Taylor and Francis Online 2018), there seems to be great potential for future research focused on inter-firm collaboration and competition via manufacturing strategy, organisation and capabilities (see, e.g. Adebanjo, Teh, and Ahmed 2018;Sarmiento, Whelan, and Thürer 2018) to find better balance between strategic, tactical and operational decisions (Meredith and Pilkington 2018). Despite this, IJPR's most frequent and recent topics remain more focused on operational contexts rather than strategic ones.…”
Section: Future Ijpr Research Opportunitiesmentioning
confidence: 99%